2020
DOI: 10.3390/app10175751
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Novel Calcia-Stabilized Zirconia (Ca-SZ) with Nano Calcium Oxide Derived from Cockle Shells and Commercial Source for Dental Application

Abstract: Various oxides are used to stabilize zirconium oxide (ZrO2), but their superior hardness causes wear of the machining tool. Calcia-doped zirconia has been studied but reports on properties suitable for dental application are lacking. Therefore, this study aimed to fabricate and characterize zirconia stabilized by calcium oxide (CaO) derived from cockle shells and compare it with zirconia stabilized by commercial CaO, sintered at different temperatures. In this study, 176 pressed pellets of zirconia mixed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The average particle sizes of CaO derived from cockle shells and commercially obtained CaO were 22-70 nm and 32-159 nm, respectively. The CaO obtained in the current study was used to stabilize zirconia, which showed good properties as a potential dental material [9].…”
Section: Fesem Analysis Of Cao Nanoparticlesmentioning
confidence: 95%
See 1 more Smart Citation
“…The average particle sizes of CaO derived from cockle shells and commercially obtained CaO were 22-70 nm and 32-159 nm, respectively. The CaO obtained in the current study was used to stabilize zirconia, which showed good properties as a potential dental material [9].…”
Section: Fesem Analysis Of Cao Nanoparticlesmentioning
confidence: 95%
“…Nanoparticles are important for producing materials with good properties [9]. The small particle size provides a larger surface area for the particles to be uniformly dispersed, and therefore may enhance the mechanical properties of the material [10], hence making the material more resistant to degradation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the microstructure and grain size distribution, the cohesive forces within the grains of the ceramic pellets are mainly influenced by particle separation, pores, and shrinkage. Hussein et al 83 found that the largest value for compressive strength was mainly found for the irregularly distributed grains. In this study, the BTO ceramic pellet exhibited a higher compressive strength value (32.91 MPa) due to the microstructure and morphology of BTO which primarily contains irregularly oriented flat block grains; this fact contributes significantly to the weakening of the bond between atoms.…”
Section: Sem Analysis Figurementioning
confidence: 99%
“…Therefore pure zirconia cannot be applied to the preparation of ceramic products. The addition of stabilizers such as Y2O3, MgO, CaO, and CeO2 is an effective measure to stabilize the tetragonal phase zirconia at room temperature [4][5][6][7]. Y2O3 is the most widely used, but yttrium oxide stabilized zirconia ceramics suffer from low-temperature ageing, which strongly limits their application in areas such as bioceramics, and there are few reserves of Y2O3, which is not conducive to sustainable development.…”
Section: Introductionmentioning
confidence: 99%